Determinants of self-care behaviors in patients with knee osteoarthritis based on the theory of planned behavior in Iran - Mohammad Ali Morowatisharifabad; Sakineh Gerayllo; Zohreh Karimiankakolaki; Ali Dehghan; Hossein Soleymani Salehabadi; Hossein Fallahzadeh (Indian Journal of Rheumatology)
Introduction: Knee osteoarthritis (OA) is one of the most prevailing causes of knee joint pains depending on age and one of the main reasons for functional deficiency. As patients are in need of effective self-care plans in promoting health, so that, this study was conducted with an aim to study the determinants of self-care behaviors in the patients with knee OA referring to clinical centers of Yazd city based on theory of planned behavior (TPB). Methods: The cross-sectional study was performed on 235 patients who referred to the health-care centers of Yazd city. A questionnaire was developed and used to collect the data based on TPB constructs. Data were analyzed using SPSS 18 software and by the statistical tests of correlative coefficient, Chi-square, and linear regression at 0.05 significance level. Results: This study was conducted on 235 patients. Based on the results of Pearson correlation test, the self-care behaviors of knee OA had a statistically significant positive correlation with all constructs of the TPB (P < 0.05). Following data analysis, the constructs of the TPB predicted 8% of the variance of intention and 16.2% of the variance of OA self-care behaviors. Conclusion: According to the results, the TPB can be suitable for explaining knee OA self-care behavior. Furthermore, recurrent training can be effective in promoting behavioral intention of patients in self-care.